One attempt of Popularization of the history of the Scandinavian countriesin Georgia - Kalandadze, Merab (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The popularization of the history of the Scandinavian countries in Georgia is relatively lame and remains a peripheral topic to this day. Of course, this does not mean that almost nothing has been done in this direction. This is not the case. Georgian historiography has made a modest contribution to the popularization of the history of the Scandinavian countries. The first or not one of the first attempts to popularize the history of the Scandinavian countries is the popular historical essay on King Gustav I Vasa of Sweden (1523-1560) published in 1901, which was translated from Russian or. Tsereteli. The choice of translator, of course, was not random. It is thought that the King of Sweden treated him as a desirable political figure for Georgia. A positive assessment of the King of Sweden’s performance is clearly not accidental, and it is, first and foremost, an echo of an understanding of the role of the individual in history. The activities of Swedish King Gustav I Vasa seem to have been in line with his political ideals. Sympathy for Gustav Vasa was not accidental and, above all, could have been conditioned by two circumstances. His name is associated with the liberation of Sweden from long Danish rule, his name is associated with the national liberation movement. The National Liberation Movement has always been a topical issue in Georgia, it has been popular and popular, we can think that they liked the reforms carried out by Gustav-Vasa, which acted as a catalyst and quickly put the newly established country on the road. Took it the right way. This was a success for King Gustav Vasa of Sweden. They tried to evaluate the work of the King of Sweden, Gustav I Vasa, from a progressive-liberal position. It was a scientific approach to the issue, which naturally has its pros and cons.